Zoonotic filariasis and its public health significance: a comprehensive literature review - M., Remya; Rahi, Manju; Saini, Prasanta (Frontiers in Microbiology, 2025)
Animal filariasis, a group of vector-borne parasitic infections, is a widely significant yet often underreported complex disease affecting a broad range of domestic and wild animals across tropical and subtropical regions. This comprehensive literature review aims to compile current knowledge on its epidemiology, pathogenesis, diagnosis, economic impact, and zoonotic implications to support improved control strategies. This review was conducted using databases such as PubMed, Scopus, and Google Scholar to collect data on filarial species, their vectors, hosts, clinical manifestations, diagnostic methods, and control measures across different geographical regions. Disease is caused by filarial nematodes belonging to order Spirurida, family Onchocercidae, which include species such as Setaria, Dirofilaria, Onchocerca, Stephanofilaria, and Parafilaria. This disease transmission primarily depends on blood sucking arthropod vectors, such as mosquitoes, blackflies, and biting midges. Distribution and involvement of these vectors influenced by environmental conditions, host availability, and regional factors. The lifecycle of all members of Onchocercidae family uniformly exhibit a similar pattern. Clinical manifestations vary depending on the host and parasites, can cause a mild to severe conditions including peritonitis, dermatitis as skin nodules, ocular infections, neurological disorders and cardiopulmonary complications. Worms have been detected in various tissues, including subcutaneous tissues, lymphatics, eye, heart, lungs, and central nervous system. Zoonotic infections have involved species from genera such as Setaria, Dirofilaria, Onchocerca, Brugia, Dipetalonema, Loaina, and Meningonema. Diagnosis of filarial infections relies on conventional methods like blood smears and skin scrapings, along with advanced molecular and serological assays for enhanced sensitivity and species identification. Control strategies include routine prophylactic treatment, vector control, and increased awareness among livestock farmers and pet owners. Filariasis in livestock causes economic losses through reduced productivity, fertility, hide quality, and treatment costs and meat condemnation. It also leads to higher management expenses, trade barriers, and decreased agricultural efficiency, particularly in endemic regions. A comprehensive understanding of intricate interactions among filarial parasites, mosquito vectors and vertebrate hosts is crucial for formulating effective prevention and control strategies. So, integrated control programs and one health approach, driven by interdisciplinary research and public health collaboration, are crucial to addressing this challenge and mitigating its zoonotic potential.